2015
DOI: 10.1590/1983-40632015v4533628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation and nitrogen fertilization on agronomic traits of sweet corn1

Abstract: Irrigation and nitrogen fertilization are management practices that have positive results for the corn crop. This study aimed at evaluating the effect of nitrogen fertilization and irrigation on agronomic traits of sweet corn. Two experiments were carried out in two crop seasons (winter/spring and summer/autumn), in a split-plot design, with the main plots consisting of four irrigation levels (50 %, 75 %, 100 % and 125 % of the crop evapotranspiration - ETc) and subplots consisting of four nitrogen doses (0 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
4
0
1
Order By: Relevance
“…These values were similar to the ones obtained by Oliveira et al (2011) and Souza et al (2015), who observed maximum values of WUE when the plant showed water deficit, with a decrease as higher water depths were applied. Cultivars Frevo and Samba showed WUE with quadratic behavior, in which the water depths which maximized this efficiency were estimated in 88% and 82.4% of crop evaporation replacement, resulting in 1.22 kg m -3 and 1.47 kg m -3 of water density, respectively.…”
Section: Resultssupporting
confidence: 90%
“…These values were similar to the ones obtained by Oliveira et al (2011) and Souza et al (2015), who observed maximum values of WUE when the plant showed water deficit, with a decrease as higher water depths were applied. Cultivars Frevo and Samba showed WUE with quadratic behavior, in which the water depths which maximized this efficiency were estimated in 88% and 82.4% of crop evaporation replacement, resulting in 1.22 kg m -3 and 1.47 kg m -3 of water density, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The values of CV and in all the variables (Table 2) were within the limits reported in the literature (Pizolato Neto et al, 2016;Silva et al, 2013Silva et al, , 2016Souza et al, 2016), what guarantees a good accuracy in the experiment. However, the CV and is not best suited to assess the accuracy of a study, since its estimates considers only the residual variance as a proportion of the average of the experiment (Resende and Duarte, 2007).…”
Section: Resultssupporting
confidence: 82%
“…The Brazilian scenario does not present great popularity for sweet corn, although edaphoclimatic conditions contribute to a productivity of more than 13.00 t ha -1 (Luz et al, 2014), the technological cultivation conditions maintain productivity below those observed in countries such as the USA, with around 17.17 t ha -1 (FAO, 2018). P r o v i s i o n o f a p p r o p r i a t e management forms allows the country to target higher productivity (Souza et al, 2015(Souza et al, , 2016 and the insertion of this product into large consumer markets. In addition, this scenario contributes to this species being inserted in rural properties as an alternative for…”
Section: Scientific Communicationmentioning
confidence: 99%